Case report: Single gene testing and comprehensive genomic profiling in non-small cell lung cancer—a case series of divergent results from a large reference laboratory - Strickland, Kyle C.; Nesline, Mary K.; Previs, Rebecca A.; Ko, Heidi; Cooper, Maureen; Rushton, Jennifer R.; Wallen, Zachary D.; Pabla, Sarabjot; Conroy, Jeffrey M.; Sausen, Mark; Saini, Kamal S.; Cantini, Luca; et al. (Frontiers in Oncology, 2024)
Clinical management of non-small cell lung cancer (NSCLC) requires accurate identification of tumor-specific genetic alterations to inform treatment options. Historically, providers have relied on single-gene testing (SGT) for actionable variants due to a perception of cost-effectiveness and/or efficient turnaround time compared to next-generation sequencing (NGS). However, not all actionable variants may be evaluated through SGT modalities, and an SGT approach can exhaust valuable tissue needed for more comprehensive analyses. In contrast, comprehensive genomic profiling (CGP) tests employ NGS to sequence megabases of DNA and RNA to evaluate all relevant molecular alterations, providing a broader genetic profile to identify actionable alterations that SGT may not accurately or efficiently assess. Here, we briefly describe four cases from a large reference laboratory in which actionable alterations were identified by CGP but not SGT. The discussion highlights the utility and advantages of using CGP to provide complete and timely treatment options and clinical trial opportunities for patients with NSCLC.